Modified atmosphere in minimally processed cauliflower conservation and quality - Furlaneto, Karina Aparecida [UNESP]; De Carvalho Mariano-Nasser, Flávia Aparecida [UNESP]; Ramos, Juliana Arruda [UNESP]; Lundgren, Giovanna Alencar; Nuvolari, Cibelli Magalhães [UNESP]; De Souza Lima, Pedro Fernandes Fleury [UNESP]; Nasser, Maurício Dominguez [UNESP]; Vieites, Rogério Lopes [UNESP] (Universidade Estadual de Londrina, 2017)
The objective of this work was to evaluate modified atmosphere effectiveness in minimally processed cauliflower aiming food safety maintenance for consumers, as conservation of product physical and chemical characteristics for better quality. Cauliflowers cv. Cindy were selected, washed, sanitized with sodium hypochlorite (200 mg L-1) and rinsed. After processing, they were immersed, one more time, in sodium hypochlorite solution (50 ppm) and dried by the air. Portions of 200 g were made and placed in different atmospheres: T1 = 0.05 % CO2 + 23 % O2; T2 = vacuum; T3 = tray of expanded polystyrene with polyvinyl chloride film (PVC) and T4 = 6 % CO2 + 4 % O2 + 90 % N2. The packages were stored in cold chamber at 5 °C ± 1 and 85% ± 5 of relative humidity. Analysis were performed every two days and the evaluated traits were: loss of fresh mass, respiratory activity, soluble solids, titratable acidity, pH, reducing sugars, instrumental color, visual and microbiological analysis. The experimental design was completely randomized, in factorial design. Data were submitted to analysis of variance and means were compared using Tukey test at 5% of probability and regression analysis for storage period. Tray of expanded polystyrene with PVC delayed for two days product climacteric peak in relation to other modified atmosphere. Furthermore, it provided quality attributes maintenance. The best notes of visual appearance and the best intention of purchase were attributed to minimally processed cauliflower wrapped in modified atmosphere with 6% CO2. + 4% O2.
Keywords: Botrytis L; Brassica oleracea var; Minimal processing; Sensory; Shelf life; Storage